THE INFLUENCE OF WORK ENVIRONMENT, JOB MOTIVATION, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE - Arifin, Zainul; Della, Prisma Della Irawati; Priyo, Didik Priyo Sugiharto (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
The research aims to examine the relationship between working environmental conditions, job motivation levels, and organizational culture on employee performance. This study focuses on the employees of PT. Indomarco Adi Prima, a company engaged in the distribution field. The research method uses a quantitative approach with a total sampling technique. Data analysis was conducted with the assistance of SPSS software. The results of the study found that the variables of Working Environment (X1), Job Motivation (X2), and Organizational Culture (X3) partially have a significant effect on Employee Performance (Y). The conclusion of this study indicates that factors such as Working Environment, Job Motivation, and Organizational Culture play an important role in improving employee performance within an organization.